EVALUATION OF PRECEPTORSHIP AND MENTORSHIP CLINICAL LEARNING METHOD ON NURSING STUDENTS' CRITICAL THINKING IN PROVIDING NURSING CARE IN A TEACHING HOSPITAL - Kurniati Puji Lestari; Muhamad Jauhar; Ike Puspitaningrum; Shobirun Shobirun; Iis Sriningsih (Poltekkes Kemenkes Semarang, 2021)
The demand for high-quality health services is increasing. It motivates nurses to utilize the best evidence in making decisions. Professional nurses were born from an excellent education. Preceptorship and mentorship clinical learning methods are expected to be able to answer these demands. This study aims to identify the effect of preceptorship and mentorship methods on students' critical thinking skills. The study design applies a quasi-experimental type pretest and post-test with a control group. Twenty-six students were examined as respondents for each intervention and control group, using a purposive sampling technique. The survey took place at a teaching hospital in Semarang, using a student-evidence-based practice questionnaire (validity 0.584-0.904; reliability 0.821) developed by Upton et al.in 2014. The intervention during three weeks with the training stages of clinical advisors, clinical guidance, internalization, and evaluation. Univariate data analysis is described by frequency and percentage (categorical) and mean and SD (numerical). Bivariate data analysis using a paired t-test and independent t-test. There was a significant effect of the preceptorship and mentorship methods on students' thinking abilities (p-value = 0.006). Integrated academic and clinical learning could form critical thinking skills among students. Educational institutions play a role in providing training for clinical instructors oriented to improving the ability of students to provide scientific evidence-based nursing care. The clinical instructors are responsible for improving students' critical thinking skills through preceptorship and mentorship learning methods.